UPAYA PENGEMBANGAN KARAKTER TANGGUNG JAWAB DAN DISIPLIN SISWA MI/SD MELALUI EKSTRAKURIKULER PRAMUKA - Adzani, Nasywa Kamila; Herianingtyas, Nur Luthfi Rizqa (LPPM Universitas Bina Bangsa, 2023)
The purpose of this research is to explain how teachers try to develop the character of responsibility and discipline through Scout extracurricular activities in elementary schools. The research method used is a qualitative method involving 14 SD/MI teachers in the Cimanggis sub-district, Depok City. Data collection was carried out through interviews and the use of questionnaires. The results showed that Scout extracurricular activities were effective in shaping the character of student responsibility and discipline through various activities such as marching training, camps, trainings, and assignments given to Scout members. The role of the teacher also has a strong significance in developing the character of responsibility and discipline through this Scout extracurricular activity